2019
DOI: 10.1111/febs.15058
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA RP11‐820 promotes extracellular matrix production via regulating miR‐3178/MYOD1 in human trabecular meshwork cells

Abstract: Primary open angle glaucoma (POAG) is the most common type of glaucoma. At the mechanistic level, POAG is thought to be caused by extracellular matrix (ECM) deposition in the trabecular meshwork (TM). Growing evidence has shown that long noncoding RNAs (lncRNAs) are involved in the fibrotic process underlying many diseases. This study was undertaken to explore the role of lncRNA‐RP11‐820 in ECM production of human TM cells (HTMCs). Our results revealed that lncRNA‐RP11‐820 was significantly upregulated under o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Increasing evidences have demonstrated that lncRNAs are involved in almost all diseases [43][44][45]. For instance, FEZF1-AS1 was revealed to be overexpressed in PDAC and promote PDAC progression and Warburg effect [27].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidences have demonstrated that lncRNAs are involved in almost all diseases [43][44][45]. For instance, FEZF1-AS1 was revealed to be overexpressed in PDAC and promote PDAC progression and Warburg effect [27].…”
Section: Discussionmentioning
confidence: 99%
“…H 2 O 2 is widely used to induce apoptosis and ECM accumulation in HTM cells by mimicking oxidative stress 36‐38 . Herein, we found that H 2 O 2 treatment repressed HTM cell viability, promoted HTM cell apoptosis and increased ECM protein (collagen I, collagen III, fibronectin, MMP3, and MMP9) levels.…”
Section: Discussionmentioning
confidence: 81%
“…Haibo Li et al [21] provided evidence that lncRNA-MALAT1 could inhibit RGC apoptosis in glaucoma through activation of the PI3K/Akt signaling pathway. Shen W. et al [22] established that oxidative stress-induced lncRNA-RP11-820 plays a key role in regulating the miR-3178/MYOD1/ECM axis in HTMCs. Moreover, our previous work [23] had proved that knockdown of lncRNA NR_003923 in human Tenon's capsule fibroblast cells (HTFs) inhibited TGF-β-induced cell migration, proliferation, fibrosis, and autophagy and overexpression of IL22RA1 enhanced HTF migration and proliferation.…”
Section: Discussionmentioning
confidence: 99%